Evolution of phytonotropes: emphasis on bacopa Monnieri - Sebastian A. Brunemeier (Psychiatry, Neurology and Medical Psychology, 2022)
Memostim® is a phytonootropic agent, containing standardized BM extract (150 mg per capsule) and Ginkgo biloba extract (120 mg per capsule), providing the whole daily dose of both components. Memostim® is registered in United Kingdom and sold in United States under trade name Memoboost®. As shown in a clinical trial of Memostim® (Memoboost®)[1], its use in the patients with dyscirculatory encephalopathy (term, commonly used in Ukraine, which corresponds more widely used term “cerebral small vessel disease”) during 3 months can ameliorate the clinical signs of this disturbance, particularly, increasing the level of neurotrophic factors (nerve growth factor-beta) up to 67%. Memostim® (Memoboost®) reduced manifestations of cognitive dysfunction, improving memory and attention. Positive influence of BM extract on the cognitive functions was followed by decreasing of manifestations of anxiety-depressive syndrome, as well increasing of the quality of life of the patients. Bacopa is a very promising medicine for cognitive dysfunction, and has a favorable safety profile with a long history of use in humans. If you or your patients suffer from cognitive dysfunction, consider performing a study on their cognitive function before and after a period of Bacopa use (>1 month is required to notice statistically significant improvements in prior clinical trials). Dosing should not be on an empty stomach, which can result in gastrointestinal upset, as Bacopa is a pro-cholinergic agent. Bacopa should be taken with food. Absorption and bioavailability of the active constituents of Bacopa, such as the bacosides, may be enhanced by co-administering a lipid such as coconut milk / medium chain triglycerides, fish oil (EPA/DHA), avocado, or other fatty foods. Bacopa can be taken any time of day, but some users report improved sleep quality when dosed prior to bed.